ARTERIAL STIFFNESS AND ITS CORRELATION WITH LABORATORY PARAMETERS AND INDICATORS OF OBESITY IN DIABETIC HYPERTENSIVE PATIENTS. (April 2021) - Novak, Ivana; Milin, Sara; Nenadic, Dora Bucan; Radic, Josipa
Abstract : Objective: Arterial stiffness can be assessed by a variety of non-invasive methods. One of the measures of arterial stiffness that has been used in clinic for some time now is pulse wave velocity (PWV). PWV can be measured with "Agedio B900" device which, in addition to measuring arterial pressure, gives information about arterial stiffness and cardiovascular age. The aim of this study was to evaluate correlations of PWV with age, laboratory parameters and indicators of obesity in Dalmatian diabetic hypertensive patients. Design and method: 106 hypertensive diabetic patients, 66 (62.3 %) men and 40 (37.7%) women, aged 69.5 (range 36-94) years were included. For each patient data about age, gender, body weight and height were collected and BMI (body mass index), WC (waist circumference) and MUAC (mid-upper circumference) were calculated. Also, values of laboratory parameters such as haemoglobin (Hg), urea, creatinine, urate, albuminuria, cholesterol and triglycerides were taken for each patient. The Agedio B900 device was used for the measurement of arterial pressure and PWV calculation. Each study subject was measured with Tanita MC780 Multi Frequency segmental body composition analyser to record whole body and segmental measurements of body composition. Results: PWV was significantly higher in patients over 65 years old than those younger than 65. Among the laboratory parameters statistically significant correlation was found only between PWV and Hg (Rho= -0.365, p = 0.02). Among the indicators of obesity, only MUAC showed significant correlation (Rho = -0.316, p = 0.01). However, statistical significance was reached after making adjustments for age, eGFR, urea, creatinine and albuminuria. All of the variables of body composition affected PWV (p < 0.001, R2 = 0.28) but BMI (p < 0.001), fat mass (p < 0.001) and muscle mass (MM) of the trunk (p < 0.001) and skeletal MM to body fat ratio (p < 0.001) stood out. Conclusions: PWV was correlated to all the variables of body composition after making adjustments for age and markers of kidney function. Future studies with larger number of participants should evaluate correlation of PWV with the observed parameters in this population of patients.